Synthesis and Characterization of Chitosan-Vermiculite Composite Beads for Removal of Uranyl Ions: Isotherm, Kinetics and Thermodynamics Studies - Senol, Zeynep Mine; Simsek, Selcuk; Ozer, Ali; Senol Arslan, Dilek (Springer, 2020)
In this study, a new material containing Chitosan (Ch)-Vermiculite (V) composite beads was synthesized with epichlorohydrin cross-linking agent and used to remove uranyl ions from the aqueous solution. The prepared new material was characterized by SEM, XRD, FTIR analyses and PZC measurement. The effects of significant parameters on adsorption including temperature, pH, concentration and time were investigated. The obtained results indicated that the new composites of Ch-V was revealed in different structure. The zeta potential analyses showed that electrostatic attraction existed during the adsorption process between the uranyl ions and Ch-V. The maximum adsorption capacity of material was calculated as 0.665 mol kg(-1) by considering Langmuir equation. Adsorption kinetic was also explained with pseudo second order and intra particular diffusion models. Experimental studies clearly showed that the adsorption was endothermic and occurred spontaneously. The newly developed smart material has many advantages such as reusability, high adsorption capacity, selectivity and economics.
Senol, Zeynep Mine/0000-0002-5250-1267; Ozer, Ali/0000-0002-4207-8207
Keywords: Chitosan; Vermiculite; UO₂²⁺; Wastewater Treatment; Adsorption; UO22+; Uo22+